THE ROLE OF BRILINK AGENTS IN IMPROVING THE ECONOMY OF RURAL COMMUNITIES WITH AN ECONOMIC APPROACH - desti Paradilla; Munawarah Munawarah; Musrini Muis (Universitas Islam Darul 'ulum Lamongan, 2025)
This study seeks to examine how BRILink agents contribute to enhancing the economic development of rural communities using an Islamic economic approach economic approach. This field study applies a qualitative approach, utilizing data collection methods such as interviews, observations, and documentation. Interviews were conducted with BRILink agents and users to obtain comprehensive data. The gathered data was analyzed using descriptive methods. The findings show that the presence of BRILink agents provides easy access to banking services, accelerates transactions, and support the growth of SMEs, thereby contributing to the welfare of society, especially farmers and SMEs. Further analysis shows that BRILink agent operations are consistent with Islamic economic values like collaboration, fairness, certainty, and advantage, the current setup requires more agents to better serve the broader population. The findings of study indicate that policies to support the development of BRILink agents in similar villages are very important to expand financial access and financial inclusion.